2005
DOI: 10.1073/pnas.0506653102
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-dependent binding of the clathrin AP2 adaptor complex to GABA A receptors regulates the efficacy of inhibitory synaptic transmission

Abstract: The efficacy of synaptic inhibition depends on the number of ␥-aminobutyric acid type A receptors (GABA A Rs) expressed on the cell surface of neurons. The clathrin adaptor protein 2 (AP2) complex is a critical regulator of GABAAR endocytosis and, hence, surface receptor number. Here, we identify a previously uncharacterized atypical AP2 binding motif conserved within the intracellular domains of all GABAAR ␤ subunit isoforms. This AP2 binding motif (KTHLRRRSSQLK in the ␤3 subunit) incorporates the major sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
247
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(258 citation statements)
references
References 40 publications
5
247
3
1
Order By: Relevance
“…In agreement with the observation that GluR2 exerts dominant effects over GluR1 with regard to AMPA receptor internalization (15), we have found that AP-2 appears to interact much more efficiently with GluR2 or GluR3 than with GluR1 CTs. Moreover, we have mapped the GluR2 binding activity to a site within 2 that is also responsible for its binding to inhibitory postsynaptic GABA A receptors (17) and to the presynaptic vesicle protein synaptotagmin (9,18), suggesting a common mechanism for recognition of pre-and postsynaptic membrane cargo proteins by AP-2. This view is also supported by our observation that increasing concentrations of inositolpolyphosphates inhibit the association of GluR2 with AP-2, similar to what has been reported before for the synaptotagmin 1-AP-2 complex (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the observation that GluR2 exerts dominant effects over GluR1 with regard to AMPA receptor internalization (15), we have found that AP-2 appears to interact much more efficiently with GluR2 or GluR3 than with GluR1 CTs. Moreover, we have mapped the GluR2 binding activity to a site within 2 that is also responsible for its binding to inhibitory postsynaptic GABA A receptors (17) and to the presynaptic vesicle protein synaptotagmin (9,18), suggesting a common mechanism for recognition of pre-and postsynaptic membrane cargo proteins by AP-2. This view is also supported by our observation that increasing concentrations of inositolpolyphosphates inhibit the association of GluR2 with AP-2, similar to what has been reported before for the synaptotagmin 1-AP-2 complex (10).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that various pre-and postsynaptic membrane receptors including AMPA and GABA A receptors (17), as well as synaptotagmin family members (9) use a common mechanism for interacting with a cognate recognition site within subdomain B of 2-adaptin (17,18) poses the question of how exactly this is accomplished and why a distinct atypical internalization signal is used for this type of cargo proteins. One possibility could be that atypical endocytosis signals within synaptic cargo membrane proteins could contribute to their sorting into specialized endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide pep␤3 was synthesized corresponding to residues 401-412 (KTHLRRRSSQLK) of the rat GABA A R ␤3 subunit. An identical peptide (pep␤-phos) chemically phosphorylated at S408/S409 was synthesized as described previously (Kittler et al, 2005). The peptide pep␤3-[S3 A] was synthesized based on the same amino acid sequence as pep␤3, except that S408/S409 were both changed to Ala (KTHLR-RRAAQLK).…”
Section: Methodsmentioning
confidence: 99%
“…For OGD treatment ACSF was replaced with OGD buffer (126 mM NaCl, 24 mM NaHCO 3, 1 mM NaH2PO4, 2.5 mM KCl, 1 mM MgCl2, 2 mM CaCl 2, 7 mM sucrose, and gassed with 95% N2/5% CO2) (42 Electrophysiology. Whole-cell recordings of mIPSCs from cortical slices, or GFP-2FYVE transfected cultured cortical cells, were performed using standard voltage clamp techniques in the presence of CNQX (20 M) and APV (40 M) to block AMPA and NMDA receptors, respectively (43,44). Membrane currents from HEK-293 cells were measured, as outlined previously at 32°C (10,43,45).…”
mentioning
confidence: 99%
“…Whole-cell recordings of mIPSCs from cortical slices, or GFP-2FYVE transfected cultured cortical cells, were performed using standard voltage clamp techniques in the presence of CNQX (20 M) and APV (40 M) to block AMPA and NMDA receptors, respectively (43,44). Membrane currents from HEK-293 cells were measured, as outlined previously at 32°C (10,43,45). Data were collected 5 min after obtaining a stable recording conformation.…”
mentioning
confidence: 99%